2018
DOI: 10.1055/s-0037-1604199
|View full text |Cite
|
Sign up to set email alerts
|

Two- versus Three-Point Internal Fixation of Displaced Zygomaticomaxillary Complex Fractures

Abstract: Despite the high frequency of the zygomaticomaxillary complex (ZMC) fractures, there is no consensus among facial reconstructive surgeons regarding the best surgical management; thus, surgical choice for ZMC fractures is still challenging. This study included 40 patients with displaced ZMC fracture. Twenty patients were treated with open reduction and internal fixation (OR/IF) using two-point fixation technique (at infraorbital margin and zygomaticofrontal buttress region) and the remaining 20 patients were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 12 publications
(19 reference statements)
2
20
0
1
Order By: Relevance
“…We did not perform more than two fixations for reduction surgery. Nasr et al [ 20 ] reported no significant difference between 2-point fixation and 3-point fixation for ME asymmetry, including zygomatic projection and width. In radiological assessment using CT scan 3 months after surgery to evaluate post-reduction displacement, backward displaced zygoma reduction in axial view was significantly better in the 2-point fixation group than in the 3-point fixation group.…”
Section: Discussionmentioning
confidence: 99%
“…We did not perform more than two fixations for reduction surgery. Nasr et al [ 20 ] reported no significant difference between 2-point fixation and 3-point fixation for ME asymmetry, including zygomatic projection and width. In radiological assessment using CT scan 3 months after surgery to evaluate post-reduction displacement, backward displaced zygoma reduction in axial view was significantly better in the 2-point fixation group than in the 3-point fixation group.…”
Section: Discussionmentioning
confidence: 99%
“…Poucos trabalhos clínicos discutem e analisam os resultados do emprego de um, dois e três pontos de fixação em pacientes com fraturas de CZO 8,17 . Em 2017, Nasr et al 18 compararam a utilização de dois e três pontos de fixação em pacientes com fraturas de zigoma. Os autores relatam que a fixação de três pontos é a técnica padrão, contudo a modalidade com dois pontos é efetiva, clinicamente imperceptível e quase tão eficaz quanto à fixação de três pontos impedindo a rotação ou deslocamento ósseo, alem de ter menor custo.…”
Section: Discussionunclassified
“…Because maxillofacial buttresses represent the bars that support the maxillofacial skeleton building, they serve as the prime locations for plate fixation during repair [1][2][3].…”
Section: Biomechanicsmentioning
confidence: 99%
“…The masseter muscles can also affect the ZMC fracture. Thus, by masseter muscles, action on the fractured segment displaces the fractured zygoma mainly downward inward with medial rotation [1][2][3].…”
Section: Biomechanicsmentioning
confidence: 99%